The Influence of Job Stress and Work Environment on Employee Performance at PT SAS Aero Sishan - Syahriza, Hendric (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to examine the influence of job stress and work environment on employee performance at PT SAS Aero Sishan, a defense technology company in Indonesia. The focus lies on addressing declining employee performance and high stress levels, particularly in a high-demand work environment. A quantitative approach was adopted, utilizing survey methods where data were collected through employee questionnaires. Job stress variables were measured using two main dimensions, namely time stress and anxiety stress, while the work environment was divided into physical and social environments. The results revealed that job stress negatively and significantly affects employee performance, while the work environment positively and significantly impacts performance. A comfortable physical environment and social support from colleagues were found to enhance productivity, although high job stress can reduce work efficiency. The study concludes that company management needs to address stress levels and create a supportive work environment to improve employee performance.